Improved Schmidt Conversion of Aldehydes to Nitriles Using Azidotrimethylsilane in 1,1,1,3,3,3-Hexafluoro-2-propanol - Hashim F. Motiwala; Qin Yin; Jeffrey Aubé (Molecules, 2015)
The Schmidt reaction of aromatic aldehydes using a substoichiometric amount (40 mol %) of triflic acid is described. Low catalyst loading was enabled by a strong hydrogen-bond-donating solvent hexafluoro-2-propanol (HFIP). This improved protocol tolerates a broad scope of aldehydes with diverse functional groups and the corresponding nitriles were obtained in good to high yields without the need for aqueous work up.